PD-1 Inhibitor Therapy in a Patient with Preexisting P-ANCA Vasculitis: A Case Report and Review of the Literature. (31st August 2020) - Ramos, Amanda; del Carmen, Marcela; Yeku, Oladapo
Abstract : Background . Recurrent endometrial cancer after definitive therapy is a lethal disease. Recently, immune checkpoint inhibitors (ICI) have improved the management of mismatch repair-deficient (MSI-H) endometrial cancer. Autoimmune side effects are known to occur with ICI. As a result, patients with preexisting autoimmune diseases are excluded from studies involving these drugs. This has led to challenges in clinical practice regarding the use of ICI in otherwise eligible patients with underlying autoimmune disease. Case Presentation . We present the case of an 81-year-old woman with an underlying autoimmune vasculitis and recurrent, metastatic endometrial adenocarcinoma with microsatellite instability, who was treated with an immune checkpoint inhibitor. This patient received pembrolizumab, an immune checkpoint inhibitor that targets the programmed cell death-1 immune checkpoint. Ultimately, she was treated for 4 months with pembrolizumab and benefited from stable disease during this period. She remained asymptomatic from her underlying autoimmune P-ANCA vasculitis. A review of the scientific literature reveals several cases of the successful use of immune checkpoint inhibitors in patients with autoimmune diseases, including systemic lupus erythematosus, rheumatoid arthritis, and inflammatory bowel disease. Conclusion . This is one of the first reports of a patient with an underlying autoimmune vasculitis successfully treated with an immune checkpoint inhibitor without exacerbating her underlying autoimmune condition. Carefully selected patients with underlying autoimmune vasculitis can be safely treated with ICI.